Position of parotid papilla and commissure of lip in relation to maxillary occlusal plane among patients visiting a tertiary care centre of Nepal - Mehta, P; Chhetri, S (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: The exact position of the Parotid papilla and commissure of the lip plays a crucial role in determining the maxillary occlusal plane which directly facilitates rehabilitating edentulous patients with a removable complete denture. Since the beginning, many authors have conducted different studies regarding its position but multiple variations in its location have been noted. Also, this type of study has not been conducted in the Nepalese population which drags the urge to determine the position of these soft-tissue landmarks in context to the Nepalese population. Objective: To determine the position of parotid papilla and commissure of lip in relation to the maxillary occlusal plane. Materials and Methods: A descriptive cross-sectional study was conducted in the 45 dentate subjects visiting Nobel medical college from November 2019 to April 2020. A vestibular impression was made, stone index fabricated and vernier caliper was used to locate position of parotid papilla & commissure of lip. All the data were collected and statistically analyzed. Results: The mean measurement of distances between maxillary occlusal plane and parotid papilla was 3.69 ± 1.19 mm and between maxillary occlusal plane and commissure of lip was 0.41 ± 0.83 mm respectively. Conclusion: This study showed that the position of the parotid papilla was superior to the position of the maxillary occlusal plane with a mean distance of 3.69mm. The commissure of lip was found to be at the level of maxillary occlusion plane in highest number of cases followed by a superior position with least at the inferior position with respect to the maxillary occlusal plane.